2008
DOI: 10.1371/journal.pbio.0060233
|View full text |Cite
|
Sign up to set email alerts
|

Caenorhabditis elegans HCF-1 Functions in Longevity Maintenance as a DAF-16 Regulator

Abstract: The transcription factor DAF-16/forkhead box O (FOXO) is a critical longevity determinant in diverse organisms, however the molecular basis of how its transcriptional activity is regulated remains largely unknown. We report that the Caenorhabditis elegans homolog of host cell factor 1 (HCF-1) represents a new longevity modulator and functions as a negative regulator of DAF-16. In C. elegans, hcf-1 inactivation caused a daf-16-dependent lifespan extension of up to 40% and heightened resistance to specific stres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
125
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(134 citation statements)
references
References 67 publications
5
125
0
1
Order By: Relevance
“…A number of additional cofactors have been identified that either positively or negatively regulate DAF-16 activity. The C. elegans host-cell factor homolog host cell factor 1 (HCF-1) interacts with and inhibits DAF-16 transcriptional activity in the nucleus (62). Consistent with this, knockdown of hcf-1 by RNAi results in increased lifespan (62).…”
Section: Smk-1mentioning
confidence: 84%
See 1 more Smart Citation
“…A number of additional cofactors have been identified that either positively or negatively regulate DAF-16 activity. The C. elegans host-cell factor homolog host cell factor 1 (HCF-1) interacts with and inhibits DAF-16 transcriptional activity in the nucleus (62). Consistent with this, knockdown of hcf-1 by RNAi results in increased lifespan (62).…”
Section: Smk-1mentioning
confidence: 84%
“…The C. elegans host-cell factor homolog host cell factor 1 (HCF-1) interacts with and inhibits DAF-16 transcriptional activity in the nucleus (62). Consistent with this, knockdown of hcf-1 by RNAi results in increased lifespan (62). In addition, the Wnt signalling pathway has been found to intersect with IIS at the level of DAF-16=FOXO, where the worm homolog of beta-catenin (BAR-1) interacts with DAF-16 required for the transcription of oxidative stress-related genes (22).…”
Section: Smk-1mentioning
confidence: 99%
“…As our data show that E2F1 directly binds to the C-terminal transcription-activation domain of FOXO3, we postulate that it acts by blocking its ability to transcriptionally activate certain FOXO3 target genes such as MnSOD and catalase. This mode of regulation by E2F1 is reminiscent to HCF-1, the C. elegans homolog of mammalian host cell factor 1, which directly binds to DAF-16 in the nucleus and negatively regulates DAF-16, possibly by preventing DAF-16 from binding to the promoters of its target genes (33).…”
Section: Discussionmentioning
confidence: 99%
“…Гены сиртуинов играют ключевую роль в регуляции скорости старения и долголетия. В частности, повсеместное подавление экс-прессии dSir2 и двух dSir2-подобных генов (CG5085 и CG6284) методом интерференции РНК в нейронах дро-зофил снижает ПЖ, а увеличение активности сиртуинов у дрожжей, червей или мух значительно продлевает ПЖ (Kusama et al, 2006;Li et al, 2008;Niedernhofer et al, 2008;Russell, Kahn, 2007). Существенное снижение МеПЖ на свету происходит и у линий с мутациями в генах семейства Hsp70.…”
Section: Discussionunclassified